Model uncertainties at MicroBooNE - Fernández, R; Del Tutto, M; Dytman, S; Furmanski, A; Jen, C (IOP Publishing, 2017)
The MicroBooNE experiment is a 170 ton Liquid Argon Time Projection Chamber (LArTPC) experiment designed for short-baseline neutrino physics, located at surface level in the Booster Neutrino Beam (BNB) at Fermilab. A muon neutrino-argon charged current (CC) cross section measurement in the energy range of ~200 MeV - 2 GeV has recently been started. These proceedings describe our first steps to understand the potential of MicroBooNE to distinguish between di?erent theories for modeling nuclear effects in neutrino scattering and the interaction model systematics that apply to MicroBooNE measurements (in particular to the muon neutrino CC event selection), before the first neutrino-argon cross sections can be derived.